STONE-FREE RATE DIFFERENCES IN KIDNEY STONES PATIENTS WITH AND WITHOUT TAMSULOSIN AFTER ESWL - Prasadja, Nindra; Soebadi, Doddy M; Djatisoesanto, Wahjoe; Pudjirahardjo, Widodo J (Indonesian Urological Association, 2011)
Objective: To determine whether the administration of tamsulosin, as adjunctive medical therapy, increases the efficacy of one session of extracorporeal shock wave lithotripsy (ESWL) to treat renal stones. Material & Method: A prospective randomized placebo controlled study enrolled 21 patients. They underwent a single ESWL session to treat solitary radiopaque renal stones 4 to 20 mm in diameter. After ESWL, the study group (11) received 0,4 mg tamsulosin daily and the control group (10) received placebo until stone clearance or a maximum period of 8 weeks. The primary endpoint was stone-free rate and parameters were stone size and clearance time. Results: The overall stone-free rate was better in the study group than in the control group (90,9% vs. 60,0%). The clearance time after 2, 4, 6 and 8 weeks was greater in the study group than in the control group (36,4%; 63,6%; 72,7% and 90,9% vs 30,0%; 50,0%; and 60,0% respectively) but statistically insignificant. Conclusion: Clinically, the results of our study have demonstrated that tamsulosin therapy, as an adjunctive medical therapy after ESWL, is more effective than lithotripsy alone for the treatment of patients with renal stones. Keywords: ESWL, tamsulosin, medical expulsive therapy, renal stones.